THE COMBINED EFFECTS OF SMALL WATER POLLUTION ON THE IMMUNE SYSTEM - Винарська, О. І.; Франчук, Ю. О.; Григоренко, Л. Є.; Лук’янчук, С. В. (Science-based technologies, 2009)
It has been observed that in the isolated actions of sodium nitrate at 0,5 LPC in rats reported increases phagosyte activity neutrophils, but only actions with sodium nitrite at 0,5 LPC — stress at the cellular level managers cells. It has been shown that the observed changes were transitory, and the effects could be identified described as adaptive response of the body’s effect on low-intensity factors. The combined effect of powder and chloroform in their oral flow in the body within a month at levels below the LPC did not cause significant irregularities in the immune status of animals.